(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
Reading is one of the aspects of language. Most ELT students find it challenging since it consists of academic phrases as well as high-level and topic based vocabularies. Most teacher tend to teach reading by explaining the words or vocabularies only, and that is not as effective as paying attention to the meaning of the passage in a deeper way. Reading well takes time, patience, and practice. This article is aimed provide with several steps that help learners to boost reading skills.